COLOUR SYMBOL IN ZHANG YIMOU’S MOVIES - Phuong, Bui Thi Thuy (VNU Journal of Foreign Studies; Vol 36 No 5DO - 10.25073/2525-2445/vnufs.4617, 2020)
Zhang Yimou is one of the most representative directors for the fifth generation of Chinese cinema. His films have earned critical acclaim from film critics and among them many have won prestigious awards in China as well as international film festivals. One of the things that appealed to his film was his unique and effective use of colors. His artistic films such as Red Sorghum, Ju Dou, and Raise the Red Lantern are the works that show his success in this respect. The paper mainly analyzes the characteristics and meaning of applying colors in the aforementioned films, and initially finds out the role of color symbol with particular art films and impression building as well as his artistic style in general.